Yes-associated protein-1 overexpression in ocular surface squamous neoplasia; a potential diagnostic marker and therapeutic target - Julius, Peter; Siyumbwa, Stepfanie N.; Maate, Fred; Moonga, Phyllis; Kang, Guobin; Kaile, Trevor; West, John T.; Wood, Charles; Angeletti, Peter C. (Frontiers in Oncology, 2023)
Yes-associated protein-1 (YAP-1) is a Hippo system transcription factor, which serves as an oncogene in squamous cell carcinoma, and several solid tumors when the Hippo pathway is dysregulated. Yet, the activity of YAP-1 in ocular surface squamous neoplasia (OSSN) has not been determined. Here, we investigate the relationship between YAP-1 overexpression and OSSN. Using a cross-sectional study design, we recruited 227 OSSN patients from the University Teaching Hospitals in Lusaka, Zambia. Immunohistochemistry was used to assess YAP-1 protein overexpression in tumor tissue relative to surrounding benign squamous epithelium. OSSN patient samples (preinvasive, n = 62, 27% and invasive, n = 165, 73%) were studied. One hundred forty-nine invasive tumors contained adjacent preinvasive tissue, bringing the total number of preinvasive lesions examined to 211 (62 + 149). There was adjacent benign squamous epithelium in 50.2% (114/227) of OSSN samples. Nuclear YAP- 1 was significantly overexpressed in preinvasive (Fisher’s (F): p <.0001, Monte Carlo (MC): p <.0001) and invasive (F: p <.0001, MC: p <.0001) OSSN in comparison to adjacent benign squamous epithelium when analyzed for basal keratinocyte positive count, staining intensity, expression pattern, and Immunostaining intensity-distribution index. YAP-1 expression did not differ between preinvasive and invasive OSSN (p >.05), keratinizing and non- keratinizing cancer (p >.05), or between T1/T2 and T3/T4 stages in invasive tumors (p >.05). However, grade 2 and 3 tumors had significantly stronger nucleus YAP-1 overexpression intensity than grade 1 tumors (F: p = .0078, MC: p = .0489). By immunohistochemistry, we identified significant overexpression (upregulation of YAP-1 protein expression) in preinvasive and invasive OSSN lesions compared to neighboring benign squamous epithelium. YAP-1 expression was significantly higher in poorly and moderately differentiated invasive squamous cancer than in well-differentiated carcinomas. Overexpression of YAP-1 within the margin of preinvasive and invasive OSSN, but not in the neighboring normal epithelium, indicates that it plays a role in the development and progression of OSSN.